Sistem Pakar Diagnosa Penyakit Pada Tanaman Seledri Menggunakan Metode ANFIS - Triana, Neni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Expert systems are computer-based information systems that use expert knowledge to achieve high-level decision performance in a narrow problem domain. MYCIN, developed at Stanford University in the early 1980's for medical diagnosis, is generally considered the most well-known expert system. Celery (Apium Graveolens L) is a leaf vegetable and medicinal plant commonly used as a cooking spice. Celery is a versatile plant, especially as a vegetable and medicine and is also used as a salad. plant disease is one of the factors that can cause crop production failure. Celery disease can attack all stages of celery development, from seed production to plant production. In this study the authors used the ANFIS method. ANFIS is an integrated fuzzy system interface mechanism that is described in a neural network architecture. The fuzzy inference system used is the first order Tagaki-Sugeno-Kang (TSK) inference system with considerations of simplicity and ease of computation. ANFIS is an adaptive system based on fuzzy logic inference that combines two methods, namely adaptive (neural method) and fuzzy method. This adaptive network is used to adapt the fuzzy logic inference system to represent the desired fuzzy interference system. The principle of the working method is to combine two methods, namely the adaptive method and the fuzzy method in which both use the same two information sources, but have different representations.